2021
DOI: 10.15587/2519-4852.2021.249312
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of surfactants with poloxamers 338 and its effect on some properties of cream base

Abstract: The aim. Study of the interaction of surfactants with poloxamer 338 (P338) and the effect of P338 on the properties of cream bases. Materials and methods. Solutions of the surfactants and P338 as well as cream bases were under study. The average hydrodynamic diameter (Dh) and zeta potential (ζ‑potential) were determined by the light scattering intensity and electrophoretic mobility of micelles. The electron paramagnetic resonance (EPR) spectra of spin probes in micelles, solvents and bases were obtained;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The dynamic viscosity of liquid paraffin (comparator liquid) was equal to 128 mPa•s at 25 °С, and τ ±1 of probe 2 was≈0.7 ns. By the calculations, the viscosity of the microenvironment of probe 2 in P338 associates was on average 2.2 times greater than the dynamic viscosity of liquid paraffin, which approximately corresponds to the viscosity of soft white paraffin [28]. In micelles of M20CE, the viscosity of the microenvironment of probe 2 was on average about 85 % of the dynamic viscosity of liquid paraffin.…”
Section: Research Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The dynamic viscosity of liquid paraffin (comparator liquid) was equal to 128 mPa•s at 25 °С, and τ ±1 of probe 2 was≈0.7 ns. By the calculations, the viscosity of the microenvironment of probe 2 in P338 associates was on average 2.2 times greater than the dynamic viscosity of liquid paraffin, which approximately corresponds to the viscosity of soft white paraffin [28]. In micelles of M20CE, the viscosity of the microenvironment of probe 2 was on average about 85 % of the dynamic viscosity of liquid paraffin.…”
Section: Research Resultsmentioning
confidence: 85%
“…Probe 2 in the micelles was in state of rapid rotation. The viscosity of its environment was about 2 times less than the viscosity of liquid paraffin (τ -1 ≈0.28 ns; τ ±1 ≈0.70 ns) [28]. Using of lipophilic probe 2 it was shown that there was BC concentration range, in which BC associates were formed before the CMC.…”
Section: Research Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…5 % poloxamer 338, 20 % macrogol 1450 and 5 % macrogol 4000 were the thickening agents in these bases (Table 2) [13,15]. The fourth group consisted of liquid and cream with a mixed structure of dispersion medium (Table 3) [4].…”
Section: Planning (Methodology) Of the Researchmentioning
confidence: 99%
“…However, the development of both novel drugs and generic/hybrid products is quite difficult, and specific problems arise on the way to their authorisation and production [2]. SSPs can represent a variety of dispersed systems with extremely complex structures [3,4]. SSPs are characterised by more complicated, interdependent relationships in their structure, physicochemical, biopharmaceutical properties and effectiveness as compared to solid dosage forms or parenteral preparations.…”
Section: Introductionmentioning
confidence: 99%